1984
DOI: 10.2166/wst.1984.0233
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Houston's Southwest Wastewater Treatment Plant, U.S.A.

Abstract: In 1981, the City of Houston's Southwest Wastewater Treatment Plant (144,000 m3/d) was experiencing occasional afternoon bulking with loss of solids to the effluent. The plant employs sludge reaeration with about even allocation of tank volume to mixed liquor and return sludge aeration. A dynamic model of solids transfer from influent to mixed liquor to settling tank to return sludge aeration and wasting was developed for use on a desk-top computer. The model predicted that a counter-intuitive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The model of Garrett et a!. (1984) was based on overflow and underflow clarifier rates and solids settling velocity.…”
Section: Sedimentation Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…The model of Garrett et a!. (1984) was based on overflow and underflow clarifier rates and solids settling velocity.…”
Section: Sedimentation Modelsmentioning
confidence: 99%
“…This concentration is much greater than would be predicted by the exponential expression. This was the primary reason for the selection of the power expression, although the comparison was not presented in the paper of Garrett et al (1984). Rachwal et al (1982) and Smollen and Ekama (1984) concluded that the exponential expression gives a better correlation between consideration of these opinions, Garrett et aI.…”
Section: Sedimentation Modelsmentioning
confidence: 99%
See 3 more Smart Citations